2019
DOI: 10.1103/physrevb.100.085202
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure as a guide in screening for potential thermoelectrics: Demonstration for half-Heusler compounds

Abstract: We adopt a high throughput search strategy that begins with electronic structure features to screen a set of half-Heusler compounds for thermoelectric performance. This is motivated by the contradictory electrical transport requirements, specifically high electrical conductivity, σ and high thermopower, S, for obtaining high figure of merit, ZT. We use an electronic fitness function that measures the extent to which a specific band structure decouples σ and S for this purpose. We then perform detailed, more co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 86 publications
0
24
0
Order By: Relevance
“…As the elements in the HH system change, the band gap can be varied within the range of 0-4 eV. [13][14][15] Thus, 18-e HH compounds with an adjustable band gap (the semiconductor behavior) are suitable for thermoelectric applications. More importantly, the unique electronic structures of HH compounds lead to high electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…As the elements in the HH system change, the band gap can be varied within the range of 0-4 eV. [13][14][15] Thus, 18-e HH compounds with an adjustable band gap (the semiconductor behavior) are suitable for thermoelectric applications. More importantly, the unique electronic structures of HH compounds lead to high electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[ 40 ] The ZT value of the RuNbAs compound can be improved by p‐type doping. In this view, Feng et al [ 40 ] have shown that ZT reaches the value of 0.9 at 1000 K for a doping of 17.75 × 10 19 cm −3 . The ZT of RuVAs material increases with increasing temperature until 0.47 at 900 K and then decreases gradually.…”
Section: Resultsmentioning
confidence: 99%
“…ZT of the RuNbAs material has a maximum value of 0.62 at 1000 K. At this temperature, the half‐Heusler compounds often exhibit good performance. [ 40 ] The ZT value of the RuNbAs compound can be improved by p‐type doping. In this view, Feng et al [ 40 ] have shown that ZT reaches the value of 0.9 at 1000 K for a doping of 17.75 × 10 19 cm −3 .…”
Section: Resultsmentioning
confidence: 99%
“…The TE electronic fitness function EFF was as described by Xing et al [65] and measured the extent to which a band structure incorporated features that decouple conductivity and thermopower to the benefit of TE performance. [66] The ceramic average Seebeck is the conductivity weighted average, S cer = (σ x S x + σS y + σ z S z )/(σ x + σ y + σ z ). The direction average EFF is the average of the EFF over the three directions.…”
Section: Methodsmentioning
confidence: 99%